2013
DOI: 10.1111/opn.12021
|View full text |Cite
|
Sign up to set email alerts
|

Issues in caregiving for older people with intellectual disabilities and their ageing family carers: a review and commentary

Abstract: Opportunities for supervision could be one way to increase individuals' awareness of their own role in the team.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
76
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 115 publications
(81 citation statements)
references
References 34 publications
4
76
0
1
Order By: Relevance
“…while in the other two groups it loaded on the third factor "Positive value". The aging family caregivers of adult daughter or son with intellectual disabilities may have poor emergency or future planning and lack of appropriate services (Ryan, Taggart, Truesdale-Kennedy, & Slevin, 2014). For example, respite services are more often an older people's residential facilities (Taggart, Truesdale-Kennedy, Ryan, & McConkey, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…while in the other two groups it loaded on the third factor "Positive value". The aging family caregivers of adult daughter or son with intellectual disabilities may have poor emergency or future planning and lack of appropriate services (Ryan, Taggart, Truesdale-Kennedy, & Slevin, 2014). For example, respite services are more often an older people's residential facilities (Taggart, Truesdale-Kennedy, Ryan, & McConkey, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Research has shown that many parents and siblings feel anxiety about the long‐term care plans for their adult relative with IDD (Davys & Haigh, ; Davys, Mitchell, & Haigh, ; Freedman, Krauss, & Seltzer, ; Weeks, Nilsson, Bryanton, & Kozma, ). Previous research has found that caregivers in this group are likely to be socially and economically disadvantaged and at greater risk than most to develop serious health issues (Black & McKendrick, ; McConkey, ; Ryan et al, ). In another study, a survey of lone caregivers reported a wide array of health issues and high levels of anxiety relating to their caregiving responsibilities (Taggart, Truesdale‐Kennedy, Ryan, & McConkey, ).…”
Section: Introductionmentioning
confidence: 90%
“…These caregivers, who are typically ageing parents, take on the non‐normative role of caring for their children from birth and childhood all the way through adulthood. In some cases, that parenting role can span up to seven decades (Ryan, Taggart, Truesdale‐Kennedy, & Slevin, ). Research has shown that many parents and siblings feel anxiety about the long‐term care plans for their adult relative with IDD (Davys & Haigh, ; Davys, Mitchell, & Haigh, ; Freedman, Krauss, & Seltzer, ; Weeks, Nilsson, Bryanton, & Kozma, ).…”
Section: Introductionmentioning
confidence: 99%
“…In another study carers have reported that they experience a range of health problems and that their caregiving role results in high levels of anxiety [37]. A recent review suggested there was going to be a 'new' population of older people with intellectual disability due to improved survival and there is an urgent need to develop services and support structures to assist these families [39] Some work has begun to identify alternatives for these often stressed and anxious families. One example is the proposal of a health home or a medical home for adults with intellectual disability [40].…”
Section: Family Levelmentioning
confidence: 99%